Censorship - Caso, Frank (New York : Facts On File, 2008)
"Providing a comprehensive overview of the different forms that censorship can take, this book examines the history and current practices of censorship in five countries - the United States, Russia, China, Zimbabwe, and Egypt - and discusses key counterstrategies. Parts II and III of the book include primary source documents relating to censorship in these five countries; biographical information on key figures whose lives were, or are, linked with censorship; and a list of U.S. and international organizations and agencies that monitor and publicize censorship activity, provide legal assistance, and develop counterstrategies. An annotated bibliography, a glossary, and a chronology complete this invaluable resource."--BOOK JACKET.
Foreword / Richard B. Collins -- Pt. I. At Issue -- Ch. 1. Introduction -- Ch. 2. Focus on the United States -- Ch. 3. Global Perspectives -- Pt. II. Primary Sources -- Ch. 4. United States Documents -- Ch. 5. International Documents -- Pt. III. Research Tools -- Ch. 6. How to Research Censorship -- Ch. 7. Key Players A to Z -- Ch. 8. Organizations and Agencies -- Ch. 9. Annotated Bibliography.
Includes bibliographical references (p. 288-303) and index.
Keywords: Censorship -- Cross-cultural studies; Censorship -- Sources; Censorship -- United States -- Sources